Investigation of aflatoxins occurrence in flavoring preparations for the alcoholic beverage industry - Laratta, Bruna; Carpentieri, Serena; Cautela, Domenico (Frontiers in Food Science and Technology, 2023)
An exploratory study was carried out to determine the occurrence of aflatoxins B1, B2, G1, and G2 in different aromatic preparations used in the production of bitters, liqueurs and flavored wines. Aflatoxin analysis was performed by liquid-liquid extraction followed by immunoaffinity column for purification of the extracts. The aflatoxins were quantitatively detected using high performance liquid chromatography technique with post-column derivatization and fluorescence detection. After in-house validation, the method was applied to the determination of aflatoxins in 40 samples of aromatic preparations used in the production of aperitifs and bitter drinks, vermouths and aromatized wines, and nut and citrus liqueurs. This method showed good accuracy between days (72%–95% recovery) and precision (3%–13% relative standard deviation). None of the samples analyzed contained detectable levels of aflatoxins. Only in one sample of aromatic extract of vermouth and aromatized wine aflatoxins B1 and G1 were found below the limit of quantification. From the results, it was concluded that these extracts for commercial purposes are safe for human consumption in terms of aflatoxin concentrations. In addition, the general outcome of the study showed that an accurate analysis of AFs can be obtained in a short time with a high sensitivity, even on difficult matrices such as hydro-alcoholic mixtures of different aromatic preparations.